Problem Directors and Corporate Risk-Taking - Bhuiyan MBU; Liu J; Alam A (John Wiley and Sons Ltd on behalf of British Academy of Management, 2023)
This study investigates the impact of a ‘problem director’ on the risk-taking propensity of a firm and its consequences for firm value. Analysing a sample of US companies, we find that corporate risk-taking propensity increases when a firm appoints a problem director. Our results are of economic significance, indicating that a one standard deviation increase in problem director's score leads to a 2.33% to 4.17% increase in corporate risk-taking. Mediation analysis reveals that a problem director increases firm risk-taking through reducing financial reporting quality. Further, a firm's risk-taking increases when a new problem director joins the board, and the damaging effect persists even after the problem director has left. Moreover, if a chief executive officer (CEO) is a problem director, s/he displays a greater predisposition for risk-taking. Moreover, when a problem director also sits on a board led by a problem CEO, we determine that the former will have an even greater propensity to take risks. Further analysis determines that the presence of problem directors damages long-term firm value in the aftermath of risk-taking behaviour. Overall, this study provides fresh evidence revealing a web of connections between a problem director, ineffective corporate governance and a decline in firm value.